Syrian Names Given in Pannonia Inferior - Fehér, Bence (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Many people in Pannonia Inferior, who had some connection with the Syrian military units of the province, had more or less evidently barbarous names. Examining 46 such names, we can find that most of them are clearly interpretable either in Syriac or in Hebraic language, or even in both of them. Sometimes we can identify orthographic variations of these names, their religious background or even some differences in those people’s use of their native language.